Effect of weekly temperature reduction on nursery pig performance - Nichols, David A.; Johnston, M.; Blecha, Frank; Murphy, James P. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 64 pigs were used to evaluate the effect of weekly temperature reductions. No differences were observed between treatments for average daily feed intake, daily gain, or feed efficiency. Pigs exposed to cooler temperatures during weeks 3 and 4 tended to consume more feed than those housed at 92 F for the entire period.
Keywords: Swine; Temperature; Nursery pig performance